2022
DOI: 10.3390/antiox11020181
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Improves Pulmonary Function and Prevents Emphysema Caused by Exposure to Cigarette Smoke in Male Mice

Abstract: Chronic obstructive pulmonary disease (COPD) is the major cause of morbidity and mortality worldwide, and cigarette smoke is a key factor in the development of COPD. Thus, the development of effective therapies to prevent the advancement of COPD has become increasingly essential. We hypothesized that quercetin protects lungs in mice exposed to long-term cigarette smoke. Thirty-five C57BL/6 mice were exposed to cigarette smoke (12 cigarettes per day) for 60 days and pretreated with 10 mg/kg/day of quercetin via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…After 24 h from the last exposure, the mice were sedated using a mixture of ketamine (100 mg/kg) and xylazine (20 mg/kg) administered intraperitoneally. The procedures for collecting ventilatory parameters were performed in regard to the methodology demonstrated by Araújo et al [ 6 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 24 h from the last exposure, the mice were sedated using a mixture of ketamine (100 mg/kg) and xylazine (20 mg/kg) administered intraperitoneally. The procedures for collecting ventilatory parameters were performed in regard to the methodology demonstrated by Araújo et al [ 6 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Relative cell count was performed under an optical microscope with immersion oil. The total and differential cell counts were performed by two trained researchers [ 27 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, this protective mechanism of quercetin is still doubtful in the lung tissue. Recently Araújo et al [ 14 ] suggested that quercetin protected alveolar structure and halted inflammation and oxidative stress in a chronic obstructive pulmonary disease induced by cigarette smoke.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to cigarette smoke is a known risk factor, 5,6 and treatments were developed to alleviate this negative effect. 7,8 Alcohol consumption is another known risk factor for COPD 9 as well as aging. 10 In this study, we aimed to explore the association of air-quality trajectories of six air-quality markers, fruit and vegetable consumption and drinking water source trajectories with COPD death rate using spatiotemporal data for Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to cigarette smoke is a known risk factor, 5 , 6 and treatments were developed to alleviate this negative effect. 7 , 8 Alcohol consumption is another known risk factor for COPD 9 as well as aging. 10 …”
Section: Introductionmentioning
confidence: 99%